Pain Energy Model of Mobility Limitation in the Older Adult. Issue 8 (22nd May 2017) - Coyle, Peter C; Schrack, Jennifer A; Hicks, Gregory E
Abstract: Background: Chronic pain is prevalent, costly, and disabling among older adults. Although mobility decline is inevitable with aging, it is clear, from current evidence, that older adults with chronic pain experience a greater rate of functional mobility decline than their pain-free peers. Past studies suggest that pain expedites the age-related decline in functional mobility; however, the pathways through which pain affects mobility remain unclear. Gerontological experts hypothesize that the age-related decline in mobility may be driven by alterations in energy expenditure; these concepts are outlined in a model known as the Energetic Pathway of Mobility Loss. Pain may play a critical role in this process through a pathway of energetic inefficiency, physical inactivity, and decreased capacity. Purpose: The purposes of this article are to 1) summarize the current literature that supports the Energetic Pathway of Mobility Loss model and 2) propose a new framework, known as the Pain Energy Model, to clarify how the disablement process may be amplified among older adults with painful conditions. Conclusion: This new framework is designed to generate new clinical research and to suggest new clinical implications for older adults with painful conditions by identifying key steps and potential treatment targets in the pathway to functional mobility decline.